2023
DOI: 10.1139/cjfas-2022-0270
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of the phenotype textures of three Thunnus species based on the machine learning SVM algorithm

Abstract: Tuna resources are an important part of China’s pelagic fishery production. However, for China’s tuna fishery, tuna species caught at sea are still manually classified, which is a time-consuming and inefficient process, so China’s tuna fishery needs to develop towards automation. This study uses GLCM (gray level co-occurrence matrix) and VGG16 to visualize phenotypic texture through local images of three Thunnus species. At the same time, texture feature index data (TFD), deep feature data (DFD) and their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In experimental evaluations, they reported that they achieved a high performance of 98.8% with ANN (Kaya et al, 2017). Ou et al (2023) proposed a two-stage study to identify the species of tuna caught in the high seas of China. In the first stage, morphological expressions were obtained from images using VGG16 and GLCM model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental evaluations, they reported that they achieved a high performance of 98.8% with ANN (Kaya et al, 2017). Ou et al (2023) proposed a two-stage study to identify the species of tuna caught in the high seas of China. In the first stage, morphological expressions were obtained from images using VGG16 and GLCM model.…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage, morphological expressions were obtained from images using VGG16 and GLCM model. Afterwards experimental evaluations were made with the SVM machine learning algorithm and as a result, they reported that they achieved a high performance of 95% in classifying the species of tuna (Ou et al, 2023). Lanjewar and Panchbhai (2023) balanced two merged but highly imbalanced datasets from Kaggle using SMOTEENN and Random Under Sampler methods.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional methods can be subdivided into out-of-water and underwater techniques. In the examination of 2D measurements of fish out of water, Ou Liguo et al [11] utilized computer vision technology to determine the positions of key points on tuna specimens. They conducted automated measurements of the pixel length of morphological features for three tuna species and calculated their actual lengths.…”
Section: Introductionmentioning
confidence: 99%
“…CNN is the most prominent deep learning method in which the multiple layers are trained and tested robustly. In recent years, deep learning has been broadly applied in various domains [ 22 ], since it autonomously extracts image features for image recognition [ 23 , 24 ]. Deep features are high-level feature representations that are learned from original image data by deeply learned models.…”
Section: Introductionmentioning
confidence: 99%